2017
DOI: 10.1016/j.joca.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for the design and execution of protocols for animal research and treatment to improve reproducibility and standardization: “DEPART well-prepared and ARRIVE safely”

Abstract: Following DEPART during the design phase will enable completion of the ARRIVE checklist at the time of publication, and thus improve the quality of evidence for inclusion of experimental animal research in meta-analyses and systematic reviews: "DEPART well-prepared and ARRIVE safely".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 99 publications
0
40
0
3
Order By: Relevance
“…The problem is not simply in the reporting but in the quality and design of the study, as argued in the review by Smith et al in this issue [1]. A false negative result is as unhelpful as a false positive result and much research funding is wasted on poorly designed studies.…”
mentioning
confidence: 99%
“…The problem is not simply in the reporting but in the quality and design of the study, as argued in the review by Smith et al in this issue [1]. A false negative result is as unhelpful as a false positive result and much research funding is wasted on poorly designed studies.…”
mentioning
confidence: 99%
“…The ARRIVE guidelines [17] for reporting animal research are akin to the CONSORT guidelines for clinical trials, and address the frequent lack of detail in how animal experiments are reported. The DEPART guidelines [8] are an example of osteoarthritis-specific considerations for how animal experiments are designed, while all NIH-supported preclinical research must now adhere to the NIH Principles and Guidelines for Reporting Preclinical Research guidelines [18]. Applying clinical trial methods to the bench, e.g.…”
Section: Problems With Reproducing Academic Results In Industrymentioning
confidence: 99%
“…This should entail an in-depth review of existing models and experimental procedures followed by open publication of standardized animal protocols and promotion of their use (e.g., preference setting by high profile journals and funding bodies), similar to the NEWMEDS initiative for schizophrenia research [39]. Scientists working in osteoarthritis research have recently published "considerations for the design and execution of protocols for animal research and treatment" [40] to complement the ARRIVE guidelines [35], and a guide has also been produced for Huntington's disease animal models [41]. A similar protocol could be developed and adopted for animal model research in dementia diseases.…”
Section: The Need To Improve Validation Of Potential Drug Targetsmentioning
confidence: 99%